A Cross sectional Study on Clinicomycological Aspects of Mucocutaneous Candidiasis in a Tertiary Care Center - Subhashini Mohan; R Madhu; C Janaki (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2018)
Background: Candida is an ubiquitious organism causing superfi cial fungal infections that are commonly encountered in clinical practice. The knowledge of the change in the epidemiology, clinical spectrum and antifungal susceptibility may aid for the appropriate treatment decisions.  Aim and Objective: To identify different candida species from various clinical patterns of mucocutaneous candidiasis Materials and Methods: A cross sectional study was conducted on 100 randomly selected patients with symptoms and signs of mucocutaneous candidiasis attending the OPD, Mycology section of Dermatology Department. Under aseptic conditions sample collection was done by skin scraping, vaginal and oral swabs. The collected samples were treated with 10% KOH and examined under the light microscope for the presence of pseudohyhae. Culture in SDA, subculture in Hichrome agar and sugar fermentation tests were done for all patients with positivity for candida in 10% KOH examination.